Timing and sequence of primary tooth eruption in children with cleft lip and palate - Tatiana Yuriko Kobayashi; Márcia Ribeiro Gomide; Cleide Felício de Carvalho Carrara (University of São Paulo, 2010)
OBJECTIVE: To determine the timing and sequence of eruption of primary teeth in children with complete bilateral cleft lip and palate. MATERIAL AND METHODS: This cross-sectional study was conducted at the Hospital for Rehabilitation of Craniofacial Anomalies of the University of São Paulo, Bauru, SP, Brazil, with a sample of 395 children (128 girls and 267 boys) aged 0 to 48 months, with complete bilateral cleft lip and palate. RESULTS: Children with complete bilateral clefts presented a higher mean age of eruption of all primary teeth for both arches and both genders, compared to children without clefts. This difference was statistically signifcant for all teeth, except for the maxillary first molar. Mean age of eruption of most teeth was lower for girls compared to boys. The greatest delay was found for the maxillary lateral incisor, which was the eighth tooth of children with clefts of both genders. Analyzing by gender, the maxillary lateral incisor was the eighth tooth to erupt in girls and the last in boys. CONCLUSION: The results suggest an interference of the cleft on the timing and sequence of eruption of primary teeth.